2018
DOI: 10.1002/ijc.31652
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial genotoxin causes virus reactivation and genomic instability in Epstein–Barr virus infected epithelial cells pointing to a role of co‐infection in viral oncogenesis

Abstract: We have addressed the role of bacterial co-infection in viral oncogenesis using as model Epstein-Barr virus (EBV), a human herpesvirus that causes lymphoid malignancies and epithelial cancers. Infection of EBV carrying epithelial cells with the common oral pathogenic Gram-negative bacterium Aggregatibacter actinomycetemcomitans (Aa) triggered reactivation of the productive virus cycle. Using isogenic Aa strains that differ in the production of the cytolethal distending toxin (CDT) and purified catalytically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…One theory is that the deficient immune system could result in physiological changes within the oral cavity that would support an altered microbiome. In humans, studies have found evidence of oral bacteria and their products [21] affecting activation and replication of Epstein-Barr virus and HIV [22], demonstrating that not only what bacteria are present, but also what they produce and how they interact with viruses may be important.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that the deficient immune system could result in physiological changes within the oral cavity that would support an altered microbiome. In humans, studies have found evidence of oral bacteria and their products [21] affecting activation and replication of Epstein-Barr virus and HIV [22], demonstrating that not only what bacteria are present, but also what they produce and how they interact with viruses may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, EBV can be reactivated by metabolic end products of periodontal pathogen, e.g., butyrate, as demonstrated by increased viral lytic mRNAs, BZLF1 and BGLF5, and ZEBRA protein expression in exposed cells, concomitantly increased acetylated histone H3 [ 57 ]. In addition, Aa CDT has been reported to reactivate latent EBV infection in EBV positive cells and promote latent infection in non-infected cells via causing genomic instability [ 59 ].…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Matching residues are also found in CdtB sequences. The importance of Mg 2+ for CdtB activity was demonstrated in AaCdtB [ 110 ], CjCdtB [ 2 ], EcCDT-II [ 111 , 115 ], HdCDT [ 116 , 117 ], StyCDT [ 74 ] through in vivo chromatin condensation and/or in vitro plasmid degradation assays.…”
Section: Structure and Function Of Bacterial Genotoxinsmentioning
confidence: 99%